Dancing with the Divine(r): Batá Drumming, Ifá Divination, and Orisha Worship in Cuba - Marcuzzi, Michael (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
This paper is an examination of similarities between batá drumming and Ifá divination among the Afrocuban socio-religious group, Lukumí. Primarily addressing the use of diametrically opposed social actions within each of these practices, the paper maintains that this juxtaposition of opposites is a constituent characteristic of divining modes—be they interpretive or mediumistic—in effecting suprahuman communication. The paper purports the necessity to examine batá drumming as a divination system; thus, it argues the need for an expanded construct of divination that can readily include musical behaviours such as possession induction.